IN ANALYSIS OF IMPACT OF UNDERLOADING OF CHP ON THE EFICIENCY OF FUEL CONSUMPTION MOLDOVA - Postolaty V.M.; Bykova E.V.; Tsaranu M.H. (Problems of the Regional Energetics, 2012)
The article presents an assessment of problems of extra-consumption of fuel resources in Moldova, as a result of underloading of CPH of national energy system, as well as, increasing share of electricity produced by condensing power plants for ensuring supply of established energy demand. It is shown that, every year, over-consumption of about 100 thou t.c.e. is observed at CHP, due to inefficient loading factor of regimes in which are forced to be operated power plants as a result of un-bounding or disconnections of some consumers of heating energy and un-coordinated policy in the field of heat supply.